PENINGKATKAN JUMLAH WIRAUSAHAWAN DI INDONESIA MELALUI KOLABORASI AKADEMISI – PELAKU USAHA – MAHASISWA - Paula Putra, Bintang (Sekolah Tinggi Ilmu Ekonomi Dewantara, 2018)
The latest published information about percentage of Indonesia’s entrepreneur from total population was 1.65% equal to 4.26 million people. This number was still lower than the minimum standard of developed countries, which is 2%. In order to achieve that number the government needs a new strategy which can effectively raise the number of new entrepreneurs which targeted the young generation. The research conducted to analyze seconder data to propose a program called a collaboration among Academics – Small and Medium Enterprises (SMEs) owners – College Students. Lead by selected lecturers, the college students were expected firstly to work together in developing existing SMEs in small groups. The next step was a program to enable them to find opportunities and open their own businesses. The last stage was the evaluations. The mentioned series of activities should be done under the Ministry of Cooperatives and SMEs of Republic of Indonesia and implemented by the departments in local districts cooperated with universities. Research objects were data of total entrepreneurs, universities, and certain data related to Indonesia’s economy. The approach of this research was deductive, which aimed to build a new theory formulated to give an idea of how to increase from existing total entrepreneurs to targeted total entrepreneurs. Both qualitative and quantitative techniques were conducted, begun with content analysis, it was followed by basic mathematical calculation. The final result of the research was a proposed program to Indonesia’s governement to gain new entrepreneurs from 1.65% to 2% as targeted.